A Facile Synthesis of ZnCo2O4 Nanocluster Particles and the Performance as Anode Materials for Lithium Ion Batteries - Pan, Yue; Zeng, Weijia; Li, Lin; Zhang, Yuzi; Dong, Yingnan; Cao, Dianxue; Wang, Guiling; Lucht, Brett L.; Ye, Ke; Cheng, Kui (Nano-Micro Letters, 2016)
ZnCo2O4 nanocluster particles (NCPs) were prepared through a designed hydrothermal method, with the assistance of a surfactant, sodium dodecyl benzene sulfonate. The crystalline structure and surface morphology of ZnCo2O4 were investigated by XRD, XPS, SEM, TEM, and BET analyses. The results of SEM and TEM suggest a clear nanocluster particle structure of cubic ZnCo2O4 ( 100 nm in diameter), which consists of aggregated primary nanoparticles ( 10 nm in diameter), is achieved. The electrochemical behavior of synthesized ZnCo2O4 NCPs was investigated by galvanostatic discharge/charge measurements and cyclic voltammetry. The ZnCo2O4 NCPs exhibit a high reversible capacity of 700 mAh g−1 over 100 cycles under a current density of 100 mA g−1 with an excellent coulombic efficiency of 98.9% and a considerable cycling stability. This work demonstrates a facile technique designed to synthesize ZnCo2O4 NCPs which show great potential as anode materials for lithium ion batteries. Highlights: 1 ZnCo2O4 nanocluster particles (NCPs) were prepared through a hydrothermal method with the assistance of sodium dodecyl benzene sulfonate (SDBS). 2 The ZnCo2O4 NCPs exhibit excellent rate performance. The initial lithiation-specific capacity of ZnCo2O4 NCPs with a current density of 100 mA g−1 reached 1110 mAh g−1 with a coulombic efficiency of 84.7 %, and a high delithiation capacity of 700 mAh g−1 was achieved over 100 cycles.